2013
DOI: 10.1002/jbmr.1991
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association and Gene Expression Profiles of TGFB1 and the Contribution of TGFB1 to Otosclerosis Susceptibility

Abstract: Otosclerosis (OTSC) is a common form of acquired hearing loss resulting from disturbed bone remodeling in the otic capsule of the middle ear. Transforming growth factor-beta1 (TGFB1) produced by osteoblasts is the most abundant growth factor in human bone. Previous studies have shown the contribution of single-nucleotide polymorphisms (SNPs) in TGFB1 toward the risk of developing OTSC in some ethnic populations. The present study was aimed at investigating the genetic association and expression profiles of TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 42 publications
(61 reference statements)
3
20
0
2
Order By: Relevance
“…Among the cytokines, TGFB1 was shown to inhibit RANKL expression and increases the OPG secretion (Murakami et al, 1998;Quinn et al, 2001). We have previously reported the genetic association of TGFB1 polymorphism with OTSC and demonstrated an increased level of TGFB1 mRNA expression in otosclerotic tissues (Priyadarshi et al, 2013). The present observation that decreased RANKL expression in OTSC tissue could be due to the inhibitory effect of TGFB1 on RANKL expression is in accordance with previous reports (Murakami et al, 1998;Quinn et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among the cytokines, TGFB1 was shown to inhibit RANKL expression and increases the OPG secretion (Murakami et al, 1998;Quinn et al, 2001). We have previously reported the genetic association of TGFB1 polymorphism with OTSC and demonstrated an increased level of TGFB1 mRNA expression in otosclerotic tissues (Priyadarshi et al, 2013). The present observation that decreased RANKL expression in OTSC tissue could be due to the inhibitory effect of TGFB1 on RANKL expression is in accordance with previous reports (Murakami et al, 1998;Quinn et al, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Scanning these loci has not identified any causative genes to date. In parallel, genetic association studies were carried out and showed the association of OTSC with polymorphisms in the COL1A1, TGFB1, BMP2, BMP4, and RELN genes in multiple populations (McKenna et al, 1998;Thys et al, 2007a;Schrauwen et al, 2008;Schrauwen et al, 2009;Khalfallah et al, 2010;Khalfallah et al, 2011;Priyadarshi et al, 2013). Gene expression profiling of disease tissue compared to controls has been suggested as a method to investigate the genetic basis of complex disorders (Xiong et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Etiopathogenesis of otosclerosis is yet unexplained, however, genetic predisposition, disturbed bone metabolism, persistent measles virus infection, autoimmunity, hormonal and environmental factors may play contributing roles in the pathogenesis of otosclerosis 2 . Genetic predisposition for disease has been recognized after the identification of ten monogenic loci (OTSC1 - OTSC5, OTSC7, OTSC8 and OTSC10); however, the causative genes within these regions are undefined till date 3 . Sporadic cases are common and genetic association studies have shown the association of COL1A1, TGFB1, BMP2, BMP4 and RELN gene with otosclerosis 3 .…”
mentioning
confidence: 99%
“…Recently, a genetic study suggested the implication of TGFß1 in otosclerosis, some variants of the TGFß1 gene being involved in an increase of the patient's susceptibility to otosclerosis. 37 Evidence of a possible association of a TGFß1 polymorphism and otosclerosis involving stapes ankylosis has been shown 38 with the implication of bone morphogenetic proteins (BMP) 2, 4, 5, and 7, which are members of the TGFß superfamily. 29, 39 BMP 5 and 7 may play a predominant role in the active part of the stapedial involvement with otosclerosis, its pattern evolving with the disease.…”
Section: Discussionmentioning
confidence: 99%